Biodegradability of Disulfide-Organosilica Nanoparticles Evaluated by Soft X‑ray Photoelectron Spectroscopy: Cancer Therapy Implications - Mekaru, Harutaka; Yoshigoe, Akitaka; Nakamura, Michihiro; Doura, Tomohiro; Tamanoi, Fuyuhiko (ACS applied nano materials, 2019)
Two kinds of organosilica nanoparticles (NPs) that were fabricated from thiol-containing precursors, (3-mercaptopropyl)trimethoxysilane (MPMS) and (3-mercaptopropyl)methyldimethoxysilane (MPDMS), are potential delivery vehicles of anticancer drugs. MPMS can form three siloxane bonds, but MPDMS forms two siloxane bonds as the maximum limit. Hence, disulfide bonds can be involved in the three-dimensional morphology of MPDMS NPs. In addition, NPs containing disulfide bonds are potentially degraded by a reduced form of glutathione (GSH). To examine reactions between the organosilica NPs and GSH, the NPs were incubated in 10 mM GSH aqueous solution at 37 °C for 7 d and the products were analyzed using field-emission scanning electron microscopy (FE-SEM), Raman spectroscopy, and soft X-ray photoelectron spectroscopy (XPS). The Raman spectra showed the presence of disulfide bonds in the MPDMS NPs and the absence of disulfide bonds in MPMS NPs. The results of XPS measurements suggested that the disulfide bonds in the outer layer of MPDMS NPs were reduced to thiol groups. FE-SEM observations of MPDMS NPs detected changes in NP morphology after the GSH incubation. These results support the idea that MPDMS NPs contain disulfide bonds and are degradable by GSH. Therefore, MPDMS NPs possess a biodegradable feature that is advantageous for clinical translation, that is, nanomedicine.